Research orientations related to guidance and counselling programmes: A content analysis study - Uzunboylu, Hüseyin; Özmen, Serdar (Anales de Psicología / Annals of Psychology, 2021)
Guidance and psychological counselling services, which are seen as an integral part of the education system, refer to the whole of systematic services offered in line with a certain plan and programme. Guidance and counselling programmes (G&CP) are of considerable importance in the provision of these services based on data and evidence and in obtaining the expected efficiency from the services. The aim of this study is to evaluate the studies on G&CP in terms of content analysis, to reveal the current situation and to determine the scientific research orientations related to these studies. With this study, it was aimed that field staff, educators and researchers should recognise the gaps in the G&CP field, gain different perspectives on their fields of study and shed light on new research in this field. The data related to this study, which was designed according to the descriptive survey model using qualitative research methodology, were obtained by document review method. In connection with the topic of research, 105 graduate thesis studies in the ProQuest Dissertations and Theses database between 2007 and 2019 and 133 journal articles in the Web of Science database were examined. The obtained data were evaluated using the descriptive content analysis method. Studies on the subject have increased in recent years and more than half of the research has been carried out in the United States. It was observed that experimental studies were conducted using the most quantitative research methodology, that more emphasis was placed on the programme evaluation process and that sample groups at different levels, especially school counsellors, were studied. Additionally, there are some findings supporting that there are more studies concerning community-based preventive and intervention programmes than school-based studies, and also supporting the fact that school-related researches are especially paying attention to investigate the effects of the programme, perceptions and experiences of the programme, programme design and programme evaluation. Finally, the results from the research findings were interpreted and the recommendations for the researchers were presented.